On the “Art of Criticism” and the unfair commentaries on Lereno Selinuntino, the “Brazilian parrot”: a study on the criticism on Domingos Caldas Barbosa, in parallel with the criticism on Machado de Assis and on Catulo (Revista da Tulha, 2020)
Domingos Caldas Barbosa (1738/40-1800), whose pseudonym is Lereno Selinuntino, is an important poet of the 18th Century, a carioca based in Lisbon, author of many cantigas, modinhas and lundus. He was the founder of the Academia de Belas Letras de Lisboa, with Belchior Curvo de Semedo Torres de Sequeira, Joaquim Severino Ferraz de Campos e Francisco Joaquim Bingre. Besides being the president of the Nova Arcádia, Caldas Barbosa was the responsible for the Almanak das Musas, an important neoclassical anthology, published in 1793, in Lisbon. Although his fame, during his life, either in the Portuguese aristocratic halls or in Brazil, amid many illiterate listeners, the criticism on his work was used to put in second place the “Brazilian parrot”, as Lereno named himself, with humour, in his Almanak. However, it has not yet been properly acclaimed one of the greatest artists of the Brazilian colonial music and literature, of which he was composer and performer, as an expert poet and musician, even for Brazil or Portugal, where he introduced genres as the modinha. This article proposes to trace, in a synthetic way, the path of the criticism on Caldas Barbosa, which received offenses including from consecrated poets with whom he has participated in many literary activities at the Conde de Pombeiro’s Palace, as Manuel Maria Barbosa du Bocage (1765-1805) and José Agostinho de Macedo (1761-1831). Likewise, it seeks to comment on Caldas Barbosa verses to verify significant poetry achievements which help the understanding on the lerenian poetic. For this, the more relevant historiographical criticism is analyzed with comments on the verses of the poet, from, mainly, the work Viola de Lereno, published in two volumes (1798; 1826). In sum, one highlights topics of the criticism on Lereno and observations on his verses, seeking to recognize in it an artistic pattern. In relation to the critic historiography, one comments also, in parallel, about the critical tradition of the lyrical and dramatic work by Machado de Assis, besides the neoterical criticism of Cicero on Catulo’s poetry, in Ancient Rome, proposing a reflection on the Criticism phenomena.